Proses Koreografi Tari Piring Rampak Baayun Sanggar Rantiang Tagok di Kota Padang - Febby Armila; Afifah Asriati (FBS Universitas Negeri Padang, 2022)
This research is useful for revealing and explaining the choreography of the Piriang Rampak Baayun Dance at the Rantiang Tagok Studio in Padang City. This research uses qualitative methods and is also driven by documentation and uses primary and secondary information. Steps to analyze information and prove information. The research shows the choreography process of the Piring Rampak Baayun dance at Sanggar Rantiang Tagok beginning with the findings of exploration, improvisation, and composition ideas. After finding ideas and ideas from the Piring Rampak Baayun dance, the choreographer thinks about the image of the dance that will be created. Exploration thought of a movement that describes a gadih nan tageh like a Minang tribal girl. Furthermore, improvisation was carried out by the choreographer when creating the Piring Rampak Baayun dance, which was an experiment with the form of movement of a dancer and various new movements with the creativity of the dance stylist. The improv session is combined with an assessment session to sort and choose which moves are suitable for the dance theme. Composition session, arrange or arrange the parts in such a way that each other is interconnected and together form a unified whole.